MEMBANGUN KEMANDIRIAN EKONOMI KELUARGA PEMULUNG TPA AIR DINGIN KOTA PADANG MELALUI PELATIHAN KETERAMPILAN PEMANFAATAN SAMPAH PLASTIK MENJADI KREASI YANG BERGUNA - Wati Wati; Meri Rahmania; Syafii Syafii; Gustia Harini (Jurnal Hilirisasi IPTEKS, 2024)
Waste management is a crucial issue. Therefore, it is important to maintain environmental cleanliness and prevent pollution. Recycling waste can have economic value, thereby enhancing the economic independence of the community. The aim of this activity is to reduce the impact of plastic waste by utilizing it creatively to increase added value. This activity was carried out at the Air Dingin Final Disposal Site (TPA) in Lubuk Minturun, Padang City. It involved 30 participants, the majority of whom were women scavengers. The activity took place at the house of the local neighborhood leader. During the activity, participants received training on how to utilize plastic waste. The community service team demonstrated how to use tools such as scissors, box cutters, tape, and cables. Practical demonstrations were provided to ensure participants understood how to transform plastic into useful creations. Throughout the activity, participants were encouraged to freely create from used plastic and collaborate on various ideas. Discussions on the importance of environmental awareness and recycling education also took place. Participants were educated on the negative impacts of plastic waste and how they can contribute to reducing this issue. The implementation team also measured the impact of the activity. Quantitatively, they monitored the amount of plastic successfully recycled and calculated the potential reduction in plastic waste. Qualitatively, they noted changes in participants' attitudes towards waste management and environmental awareness. After the activity concluded, evaluations were conducted for future improvements. Discussions on what was successful and what needed improvement helped identify opportunities for enhancement.